Shared national identification in Northern Ireland: An application of psychological models of group inclusion post conflict. (September 2014) - Lowe, Robert D.; Muldoon, Orla T.
The common ingroup identity model (CIIM) holds that viewing former outgroup members as part of a larger shared ingroup can allow social categorisation to be harnessed for social cohesion. The ingroup projection model (IPM) suggests that even where shared identification occurs, social divisions can be transposed into superordinate groups. Here we explore the potentially inclusive national identity in a region (Northern Ireland) which has historically seen a high polarisation of identities. Using three data sets ( N = 2000; N = 359; N = 1179), we examine the extent to which a superordinate inclusive national identity, Northern Irish, is related to conciliatory attitudes. We find a common ingroup identity is linked to more positive social attitudes but not to more positive political attitudes. We conclude by considering the complexities of applying psychological models in the real world where structural and historical social divisions and vexing oppositional political questions can be transposed into new social and political orders.